"My ancestors welling in me": sound and silence in the Salt Lake Tabernacle. Issue 2 (2nd July 2020) - Peters, John Durham
ABSTRACT: The Salt Lake (or Mormon) Tabernacle in Salt Lake City, Utah has been the object of religious, scientific, and cultural fascination since its construction in the 1860s. To this day, visitors are treated to a pin-drop performance that demonstrates the building's unique acoustic properties. The building, whose history stretches from pioneer auditorium to broadcasting facility, has anchored a cross-generational soundscape that is at once architectural, musical, oratorical, political, and religious. Its soundscape echoes well over a century with both choral hymns and physical, even metaphysical silences. This article traces the story of that soundscape and demonstrates the relevance of the history of ideas as a method in sound studies.